Meningkatkan Kepercayaan Diri Anak di Panti Asuhan Muhammadiyah Koto Baru Kabupaten Solok - Dina Rahmadani; Fadhilla Yusri; Amna Amna (Concept: Journal of Social Humanities and Education, 2024)
Self-confidence is a very important indicator of success in a person's activities. However, what cannot be avoided is the level of self-confidence that each child has. Because their backgrounds are so different from other children, they are less likely to feel like they are in an orphanage. In general, the family must play an important role in the development of the child's personality, one of which is building the child's independence. However, not all children are lucky to have a complete family for life, due to loss of a family member, lack of money, financial problems, and so on. Based on interviews with adoptive mothers and adoptive fathers, it is known that it is very difficult to increase a child's self-confidence because the child's personality is not yet harmonious. Not all children are able to express their opinions and feel embarrassed or anxious during activities. Observations also show that children's self-confidence is still relatively low, but children in orphanages still feel anxious about expressing their opinions because they are afraid of answering incorrectly. Therefore, they often remain silent when asking questions because they are afraid of being laughed at by their friends. The aim of this research is to increase the self-confidence of children at the Muhammadiyah Koto Baru Orphanage, Solok Regency in expressing opinions and answering questions without feeling embarrassed or suspicious. This research uses a qualitative descriptive research method.